Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Certainly! Let's solve the equation step-by-step:
[tex]$\sqrt{5a + 2} - \sqrt{7a - 8} = 0$[/tex]
Here's the process to solve it:
1. Isolate one of the square root terms: We start by isolating one of the square root expressions on one side of the equation.
[tex]\[ \sqrt{5a + 2} = \sqrt{7a - 8} \][/tex]
2. Square both sides: To eliminate the square roots, we square both sides of the equation.
[tex]\[ (\sqrt{5a + 2})^2 = (\sqrt{7a - 8})^2 \][/tex]
This simplifies to:
[tex]\[ 5a + 2 = 7a - 8 \][/tex]
3. Solve for [tex]\( a \)[/tex]: Now, let's solve this linear equation for [tex]\( a \)[/tex].
[tex]\[ 5a + 2 = 7a - 8 \][/tex]
Subtract [tex]\( 5a \)[/tex] from both sides:
[tex]\[ 2 = 2a - 8 \][/tex]
Add 8 to both sides:
[tex]\[ 10 = 2a \][/tex]
Finally, divide both sides by 2:
[tex]\[ a = 5 \][/tex]
4. Verify the solution: It's important to verify that our solution satisfies the original equation.
Plug [tex]\( a = 5 \)[/tex] back into the original equation:
[tex]\[ \sqrt{5(5) + 2} - \sqrt{7(5) - 8} = 0 \][/tex]
Simplify inside the square roots:
[tex]\[ \sqrt{25 + 2} - \sqrt{35 - 8} = 0 \][/tex]
[tex]\[ \sqrt{27} - \sqrt{27} = 0 \][/tex]
[tex]\[ 0 = 0 \][/tex]
The solution satisfies the original equation, so [tex]\( a = 5 \)[/tex] is indeed the correct answer.
Thus, the solution to the equation is:
[tex]\[ a = 5 \][/tex]
[tex]$\sqrt{5a + 2} - \sqrt{7a - 8} = 0$[/tex]
Here's the process to solve it:
1. Isolate one of the square root terms: We start by isolating one of the square root expressions on one side of the equation.
[tex]\[ \sqrt{5a + 2} = \sqrt{7a - 8} \][/tex]
2. Square both sides: To eliminate the square roots, we square both sides of the equation.
[tex]\[ (\sqrt{5a + 2})^2 = (\sqrt{7a - 8})^2 \][/tex]
This simplifies to:
[tex]\[ 5a + 2 = 7a - 8 \][/tex]
3. Solve for [tex]\( a \)[/tex]: Now, let's solve this linear equation for [tex]\( a \)[/tex].
[tex]\[ 5a + 2 = 7a - 8 \][/tex]
Subtract [tex]\( 5a \)[/tex] from both sides:
[tex]\[ 2 = 2a - 8 \][/tex]
Add 8 to both sides:
[tex]\[ 10 = 2a \][/tex]
Finally, divide both sides by 2:
[tex]\[ a = 5 \][/tex]
4. Verify the solution: It's important to verify that our solution satisfies the original equation.
Plug [tex]\( a = 5 \)[/tex] back into the original equation:
[tex]\[ \sqrt{5(5) + 2} - \sqrt{7(5) - 8} = 0 \][/tex]
Simplify inside the square roots:
[tex]\[ \sqrt{25 + 2} - \sqrt{35 - 8} = 0 \][/tex]
[tex]\[ \sqrt{27} - \sqrt{27} = 0 \][/tex]
[tex]\[ 0 = 0 \][/tex]
The solution satisfies the original equation, so [tex]\( a = 5 \)[/tex] is indeed the correct answer.
Thus, the solution to the equation is:
[tex]\[ a = 5 \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.